Immunogenicity of recombinant Omp16 protein of Pasteurella multocida B:2 in mouse model - SHIVACHANDRA, S B; KUMAR, A; MOHANTY, N N; YOGISHARADHYA, R (The Indian Journal of Animal Sciences, 2017)
Bacterial peptidoglycan-associated lipoproteins (PAL) are potential targets for the development of diagnostics/subunit vaccines for infectious diseases. Most commonly prevalent Omp16 lipoprotein is absolutely conserved among Pasteurella multocida strains, which are involved in multiple infectious diseases of livestock worldwide. In the present study, we cloned omp16 gene encoding for mature Omp16 of P. multocida B:2 strain P52 and overexpressed as a fusion protein in Escherichia coli. Mice immunized with purified recombinant non-lipidated Omp16 fusion protein (~32 kDa) resulted in elicitation of significant antigen specific serum antibody titres (total IgG and subtypes). A more pronounced increase in Th2 response (IgG1) was noticed. The study indicated the potential possibilities to use lipidated recombinant Omp16 protein in developing a composite subunit vaccine along with suitable adjuvant for haemorrhagic septicaemia/ pasteurellosis in livestock.